The Influence of Caffeine Consumption and the Polymorphisms of DRD2 and ADORA2A Genes on Fine Motor Task Performance - McCoy, Melissa M; Beverage, Abigail; Caldwell, Rachel; Luckenbill, Courtney; Shin, Michael; Kieffer, Harold S (The FASEB journal, 2022)
Caffeine is the most commonly used psychoactive drug and has been associated with increased attention, focus and motor activity through adenosine receptor (ADORA2A) antagonism. ADORA2A and DRD2 are co-localized in the central nervous system and blocking the adenosine receptor has been show to act as a dopamine receptor (DRD2) agonist which influence focus and motor tasks. Finally, single nucleotide polymorphisms of ADORA2A varies in response to caffeine which may influence the dopamine response. The purpose of this study was to determine the influence of caffeine as well as the effects of the adenosine (ADORA2A) and dopamine (DRD2) polymorphisms during unilateral and bilateral motor tasks. Thirty-four subjects (age: 18-23) were recruited and gave informed consent to participate in the study. An oral bolus of caffeine (CAF), 5mg•kg , or placebo (PLA), maltodextrin, was given in a double-blind, randomized, and counterbalanced design 60 min prior to testing. The Purdue Pegboard Test (PPT) was used to assess the unilateral movements by placing pegs with the right hand and left hand; this was coded for dominant and non-dominant. Bilateral movements were also assessed with PPT by placing pegs with both hands and during a peg/washer/collar assembly task. Buccal cells were obtained using a 0.9% NaCl mouth rinse, spun down, and lysed via proteinase k. DNA was extracted using QiAmp Mini spin columns with amplification and allelic discrimination for ADORA2A (rs5751876) and DRD2 (rs1800497) obtained via One-Step qPCR. All samples were run in duplicate with negative and positive controls. Data was analyzed using a 2 (condition) x 2 (SNP) with repeated measures for each subset of the PPT and a 2 (condition) x 2 (ADORA2A) x 2 (DRD2) with repeated measures to for each subset to find the interaction of ADORA2A and DRD2, p<0.05) RESULTS: For the ADORA2A SNP, the main effect of caffeine demonstrated a significant increase in performance for each unilateral task from placebo to caffeine trials, dominant hand (16.4+1.6 to 17.4, p<0.01), non-dominant hand, (15.8+1.8 to 16.0, p<0.05) and combined (45.5+4.3 to 46.2, p<0.05). No difference was found for the bilateral movements. ADORA2A interaction effects demonstrated that TT genotype scored better under the caffeine condition, 15.8+1.9 to 16.2+ 0.8 for placebo and caffeine respectively. For DRD2, there were no significant differences in the main effects or interaction effects. The 3-way ANOVA, condition x ADORA2A x DRD2, demonstrated no significant differences for the main effects or interaction effects. A bolus of caffeine improved performance for the test subset scores that involved unilateral movements but had no influence on scores for bilateral movements. The reduction in performance could be due to slower reaction times or neural coupling to coordinate movements between the limbs during bilateral movements. The increased performance in the non-dominant hand for the TT genotype may be due to the increased sensitivity of this specific SNP to caffeine. While not significant, variations in responses to caffeine were observed when assessing task performance by grouped ADORA2A/DRD2 polymorphisms and the possible combinations. One grouping, TC/CC:AG/AA, demonstrated negative response to caffeine, whereas two other groupings (TT:GG, TC/CC:GG) demonstrated positive responses to caffeine. Further research and an increased sample size will help demonstrate the specific SNP interactions.